2004
DOI: 10.1246/cl.2004.830
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optical Properties of Novel Nickel Disulfide Dendritic Nanostructures

Abstract: Dendritic NiS2 nanostructures are successfully synthesized for the first time via the reaction between NiCl2·6H2O and CS2 in poly(MMA-co-EA) gel using γ irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…3 Having long-term stability and abundant presence in earth, metal dichalcogenides with structure MX 2 (where M = Fe, Mo, Co, Ni, and X = Se, S) are interesting materials to examine as well. Among these NiS 2 has good electronic, 9 magnetic, 10 and optical 11 properties. NiS 2 nanostructures have also applications in supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Having long-term stability and abundant presence in earth, metal dichalcogenides with structure MX 2 (where M = Fe, Mo, Co, Ni, and X = Se, S) are interesting materials to examine as well. Among these NiS 2 has good electronic, 9 magnetic, 10 and optical 11 properties. NiS 2 nanostructures have also applications in supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…11 A solvothermal method has also been used to prepare NiS 2 dodecahedrons and microspheres 15 and cubic shaped NiS 2 . 16 Wang et al reported the hydrothermal synthesis of NiS 2 microspheres.…”
Section: Introductionmentioning
confidence: 99%
“…Here in we synthesized pyrrole based nickel dithiocarbamate complexes, which are designed to coordinate anions via their pyrrole NH groups, precluding direct metal in coordination to the deprotonated pyrrole nitrogen atom. [9][10][11][12][13] Nickel sulfides posses electronic, 14 electrical magnetic 15 and optical properties 16 and can be used in various fields such as cathode materials in rechargeable lithium batteries, 17 catalysts for hydride nitrogen and hydro desulfurization 18,19 and IR detectors. [6][7][8] Nickel sulfides can form various compositions such as NiS, Ni 3+x S 2 , Ni 3 S 2 , Ni 7 S 6 , Ni 9 S 8 , Ni 3 S 4 , NiS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Nickel sulfides can form various compositions such as NiS, Ni 3+x S 2 , Ni 3 S 2 , Ni 7 S 6 , Ni 9 S 8 , Ni 3 S 4 , NiS 2 . [9][10][11][12][13] Nickel sulfides posses electronic, 14 electrical magnetic 15 and optical properties 16 and can be used in various fields such as cathode materials in rechargeable lithium batteries, 17 catalysts for hydride nitrogen and hydro desulfurization 18,19 and IR detectors. 20 Nickel dithiocarbamate complexes have been used as single source precursors for synthesis of nickel sulfide nanoparticles and are often influenced by the precursor.…”
Section: Introductionmentioning
confidence: 99%
“…8) In this context, 3d transition metal disulfides have drawn considerable attention because of their technological importance in catalysis, lubrications, battery fabrication, cathode materials for high energy density batteries, and other applications. 9,10) Bi 2 Se 3 has a smaller band gap (0.3 eV) 11) than TiO 2 (3.2eV), thereby making it possible to use Bi 2 Se 3 as a photosensitizer for TiO 2 by injecting the conduction band electrons from Bi 2 Se 3 to TiO 2 .…”
Section: Introductionmentioning
confidence: 99%